2022
DOI: 10.1038/s43705-022-00176-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel bacterial taxa in a minimal lignocellulolytic consortium and their potential for lignin and plastics transformation

Abstract: The understanding and manipulation of microbial communities toward the conversion of lignocellulose and plastics are topics of interest in microbial ecology and biotechnology. In this study, the polymer-degrading capability of a minimal lignocellulolytic microbial consortium (MELMC) was explored by genome-resolved metagenomics. The MELMC was mostly composed (>90%) of three bacterial members (Pseudomonas protegens; Pristimantibacillus lignocellulolyticus gen. nov., sp. nov; and Ochrobactrum gambitense sp. no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Another gene of interest from this space was S80_1a7091_mxb_fly_p.002 ~ BEPAJJ_15120, carried by a MAG classified as Ochrobactrum_B sp014138095 . This MAG was abundant in the minimal lignocellulolytic consortium constructed by Rodríguez and colleagues for lignin and plastics transformation 55 . Ochrobactrum has previously been reported to degrade UV-treated low-density polyethylene; however, this study identified the corresponding organism(s) only at the 16S level 86 .…”
Section: Resultsmentioning
confidence: 98%
“…Another gene of interest from this space was S80_1a7091_mxb_fly_p.002 ~ BEPAJJ_15120, carried by a MAG classified as Ochrobactrum_B sp014138095 . This MAG was abundant in the minimal lignocellulolytic consortium constructed by Rodríguez and colleagues for lignin and plastics transformation 55 . Ochrobactrum has previously been reported to degrade UV-treated low-density polyethylene; however, this study identified the corresponding organism(s) only at the 16S level 86 .…”
Section: Resultsmentioning
confidence: 98%
“…In conclusion, FunGeneTyper provides an innovative and unified framework with deep learning models (i.e., FunTrans and FunRep), expandable classifier toolkits (e.g., ARGTyper and VFGTyper) and customizable structured databases for the ultra-accurate classification and discovery of functional genes (e.g., ARGs and VFGs) that have scientific and biotechnological significance. This framework will contribute to the robust monitoring of function genes and discovery of novel enzymatic resources from diverse microbiomes and uncultured microbes therein, which is critical to understand and harness the microbiome sciences underlying environment (biogeochemistry, bio-restoration, and bioremediation) 14 bioeconomy (bioenergy and bioresources) 13 , and human systems (food and health) 20, 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is crucial to develop intelligent and accurate classification paradigm and bioinformatic tools to overcome limitations of existing SA-based classification approaches. Importantly, this endeavor will accelerate discovery of new genes in future metagenomic-based environmental and human microbiome studies 13, 14 .…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignocellulose, the most abundant biopolymer on earth, is composed of two carbohydrate polymers, cellulose (9–80%) and hemicellulose (10–50%), and lignin (5–35%), a heteropolymer of aromatic units. , Cellulose and hemicellulose, both of which are polymers of sugars, can be easily metabolized by soil microbes, but lignin is considered highly recalcitrant to biodegradation . However, several bacteria and fungi produce extracellular oxidative enzymes that can depolymerize lignin, thereby providing lignin derivatives for further metabolism by a subset of microbes with pathways for aromatic carbon catabolism. Pseudomonas species, which represent important members of the Gammaproteobacteria widely present in soil microbial communities, , are able to metabolize sugars as well as lignin-related aromatic derivatives such as p -coumarate, ferulate, vanillate, and 4-hydroxybenzoate. Therefore, given the ubiquity and metabolic versatility of Pseudomonas species, they present ideal candidate species for probing the bacterial metabolism underlying the ssCUE of lignocellulose-related compounds.…”
Section: Introductionmentioning
confidence: 99%